Long-term Outcome after Thrombolysis for Acute Lower Limb Ischaemia. (June 2017) - Grip, O.; Wanhainen, A.; Acosta, S.; Björck, M.
Abstract : Objectives: The purpose was to study long-term outcome after thrombolysis for acute arterial lower limb ischaemia, and to evaluate the results depending on the underlying aetiology of arterial occlusion. Methods: This was a retrospective study of patients entered into a prospective database. Patients were identified in prospective databases from two vascular centres, including a large number of variables. Case records were analysed retrospectively. Through cross linkage with the Population Registry 100% accurate survival data were obtained. Between January 2001 and December 2013, 689 procedures were included. The aetiology of ischaemia was graft/stent/stent graft occlusion in 39.8%, arterial thrombosis in 27.7%, embolus in 25.1% and popliteal aneurysm in 7.4%. Results: The mean follow-up was 59.4 months (95% CI, 56.1–62.7), during which 32.9% needed further re-interventions, 16.4% underwent amputation without re-intervention, and 50.7% had no re-intervention. The need for re-intervention during follow-up was 48.0% in the graft/stent occlusions group, 34.0% of the popliteal aneurysm group, 25.4% in the thrombosis group, and 16.3% in the embolus group ( p < .001). The overall primary patency rates were 69.1% and 55.9% at 1 and 5 years, respectively. Primary patency at 5 years was higher for the embolus group (83.3%, p = .002) and lower for the occluded graft/stent group (43.3%, p < .001). Secondary patency rates were 80.1% and 75.2% at 1 and 5 years, respectively, without difference between the subgroups. The amputation rate was lower in the embolic group at 1 and 5 years (8.1% and 11.1%, respectively, p = .001). Survival was higher in the group with occluded popliteal aneurysms at 5 years (83.3%, p = 0.004). Amputation free survival was 72.1% and 45.2% at 1 and 5 years; lower in the occluded graft/stent group at five years (37.9%, p = .007). Conclusion: Intra-arterial thrombolytic therapy achieves good medium and long-term clinical outcome, reducing the need of open surgical treatment in most patients.